Rethinking European immigration waves and conclusions for the modernization and corporatization of Ukrainian large state-owned enterprises - Kosenko, Viktor; Tymokha, Denys; Kosenko, Alisa (Theory and Practice of Public Administration, 2024)
The paper is dedicated to rethinking European immigration waves and drawing conclusions for the modernization and corporatization of large state-owned enterprises in Ukraine. This is significant for developing effective strategies for integrating migrants, enhancing management transparency, and ensuring sustainable economic development in Ukraine, as well as for implementing European practices and developing new digitalized Ukrainian practices of transparency and accountability in managing state-owned enterprises. The article begins with a review of the European experience of two immigration waves over the past 30 years, which created “immigration shocks” and contributed to a sharp increase in public attention to immigration issues, as well as structuring political competition on both the supply and demand sides of democratic representation. Based on this, the author’s vision is proposed on how this European experience can be applied to the not very popular among scholars and politicians in Ukraine and the EU, but economically significant for Ukraine, theme of promoting broad modernization of Ukrainian society and, in particular, supporting the corporatization of large state-owned enterprises, such as JSC “Ukrzaliznytsia”. The conclusion is made that state-owned corporations in Ukraine, facing a shortage of labor due to war and migration, can adapt the EU’s experience in managing migration to solve their staffing problems: a) develop targeted programs to attract qualified personnel from abroad, including the Ukrainian diaspora; b) create attractive working conditions and social packages to retain existing employees and attract new ones; c) invest in training and qualification improvement programs for local employees; d) implement more automation and digitalization processes to reduce dependence on manual labor; e) cooperate with the government to develop special visa programs for attracting foreign specialists in critically important sectors.